"Of stupidity or folly": Thomas Willis's perspective on mental retardation. Issue 6 (1st December 2002) - Williams, A N
Abstract : "Mental retardation" is a modern term for an age old problem. The descriptions of paediatric cases contained within the works of Thomas Willis (1621–75) have been increasingly recognised for their insight into seventeenth century child health practices.